The unique interplay between copper and zinc during catalytic carbon dioxide hydrogenation to methanol - Maxim Zabilskiy (Nature Portfolio, 2020)
In spite of numerous works, the nature of high activity of Cu/ZnO catalyst in methanol synthesis remains the subject of intensive debate. Here, the authors study the carbon dioxide hydrogenation mechanism using high-pressure operando techniques which allow them to unify different, seemingly contradicting, models.